2014
DOI: 10.1073/pnas.1407337111
|View full text |Cite
|
Sign up to set email alerts
|

Molecular genetic framework for protophloem formation

Abstract: The phloem performs essential systemic functions in tracheophytes, yet little is known about its molecular genetic specification. Here we show that application of the peptide ligand CLAVATA3/EMBRYO SURROUNDING REGION 45 (CLE45) specifically inhibits specification of protophloem in Arabidopsis roots by locking the sieve element precursor cell in its preceding developmental state. CLE45 treatment, as well as viable transgenic expression of a weak CLE45 G6T variant, interferes not only with commitment to sieve el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

16
292
1
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 173 publications
(311 citation statements)
references
References 24 publications
16
292
1
2
Order By: Relevance
“…The two plasma membrane-associated proteins OCTOPUS (OPS) and BREVIS RADIX (BRX) are expressed in procambium and protophloem precursors, respectively, and are required for the correct specification of protophloem cells (Scacchi et al, 2010;Truernit et al, 2012). In sieve tube element precursors, the CLAVATA3/EMBRYO SURROUNDING REGION45 (CLE45) peptide inhibits early protophloem development by signaling through the LRR-RLK receptor BARELY ANY MERISTEM3 (BAM3) (Depuydt et al, 2013;Rodriguez-Villalon et al, 2014). In support of these genes having a similar role during secondary vascular development, we identified that the closest homologs of OPS (PtOPSs; Supplemental Data Set 9) were highly expressed across the cambium, whereas genes homologous to BRX, CLE45, and BAM3 were highly expressed in the differentiating phloem (sample cluster i; Figure 4A).…”
Section: Similarities In the Regulation Of Early Vascular Differentiamentioning
confidence: 99%
“…The two plasma membrane-associated proteins OCTOPUS (OPS) and BREVIS RADIX (BRX) are expressed in procambium and protophloem precursors, respectively, and are required for the correct specification of protophloem cells (Scacchi et al, 2010;Truernit et al, 2012). In sieve tube element precursors, the CLAVATA3/EMBRYO SURROUNDING REGION45 (CLE45) peptide inhibits early protophloem development by signaling through the LRR-RLK receptor BARELY ANY MERISTEM3 (BAM3) (Depuydt et al, 2013;Rodriguez-Villalon et al, 2014). In support of these genes having a similar role during secondary vascular development, we identified that the closest homologs of OPS (PtOPSs; Supplemental Data Set 9) were highly expressed across the cambium, whereas genes homologous to BRX, CLE45, and BAM3 were highly expressed in the differentiating phloem (sample cluster i; Figure 4A).…”
Section: Similarities In the Regulation Of Early Vascular Differentiamentioning
confidence: 99%
“…Each phloem pole comprises two distinct cell types: the sieve elements, which are the actual conductive cells of the phloem; and the companion cells, which provide essential metabolic functions to the enucleated sieve elements (Lucas et al, 2013). The early, initial phloem is called protophloem and is the first tissue to differentiate in the root meristem (Furuta et al, 2014;Rodriguez-Villalon et al, 2014). It reaches from close to the stem cell niche up into the maturation zone of the meristem, where its function is gradually taken over by the neighboring metaphloem (which differentiates once the protophloem is mature) (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Sieve element differentiation is a complex process during which nuclei are broken down and cell walls are thickened (Furuta et al, 2014;RodriguezVillalon et al, 2014;Truernit et al, 2012). Genetic studies in Arabidopsis have identified two genes that promote the commitment of precursor cells to the sieve element differentiation program (Rodriguez-Villalon et al, 2014;Truernit et al, 2012): BREVIS RADIX (BRX) and OCTOPUS (OPS). Both encode different plantspecific plasma membrane-associated proteins, which are expressed in the developing protophloem and polar localized at the root-ward (BRX) or shoot-ward (OPS) end of cells (Scacchi et al, 2009;Truernit et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations